2012
DOI: 10.1074/jbc.r112.357194
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Serine: An Often Neglected but Indispensable Amino Acid

Abstract: Serine is generally classified as a nutritionally nonessential (dispensable) amino acid, but metabolically, serine is indispensible and plays an essential role in several cellular processes. Serine is the major source of one-carbon units for methylation reactions that occur via the generation of S-adenosylmethionine. The regulation of serine metabolism in mammalian tissues is thus of critical importance for the control of methyl group transfer. In addition to the well known role of D-serine in the brain, L-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
219
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(223 citation statements)
references
References 39 publications
4
219
0
Order By: Relevance
“…In the group of patients with RCC, we found elevated concentrations of serine and glycine. This finding is in line with a study of anabolic pathways for proteins, nucleic acids and lipids which are crucial to cancer cell growth (35).…”
Section: Discussionsupporting
confidence: 74%
“…In the group of patients with RCC, we found elevated concentrations of serine and glycine. This finding is in line with a study of anabolic pathways for proteins, nucleic acids and lipids which are crucial to cancer cell growth (35).…”
Section: Discussionsupporting
confidence: 74%
“…The GSH-dependent antioxidant response of cancer cells may benefit depending on the availability of serine, which can be transformed into glycine through the serine hydroxymethyltransferase (SHMT). [104][105][106] Interestingly, it has been demonstrated that cancer cells lacking p53 are protected from oxidative stress-induced by serine depletion in the presence of p73, a p53 family member that has the ability to drive serine biosynthesis de novo 107,108 and to increase the pentose phosphate shunt and nucleotide biosynthesis via G6PD. 109,110 Thus, the p73 overexpression detected in various primary RMS samples 111 may have an important role for oxidative stress resistance.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 99%
“…Also critical for cell proliferation are serine and glycine, two non-essential amino acids in mammals [9,10], which are known for their functions in phospholipid synthesis and cystathionine formation in central nervous system [11,12]. Interestingly, it has been reported recently that these two amino acids play important roles in cancer progression [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%